Sociodemographic and reproductive risk factors associated with metabolic syndrome in a population of Brazilian women from the city of Ribeirão Preto: a cross-sectional study - Ênio Luis Damaso; Heloisa Bettiol; Viviane Cunha Cardoso; Mariane Nunes de Nadai; Elaine Christine Dantas Moisés; Carolina Sales Vieira; Ricardo Carvalho Cavalli (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective: To identify sociodemographic and reproductive risk factors associated with MetS in women in their fourth decade of life. Methods: Cohort study conducted on women born from June 1978 to May 1979 in Ribeirão Preto, Brazil. Sociodemographic, clinical, and obstetric data were collected by interview and clinical evaluation. Univariable and multivariable binomial logistic regression models were constructed to identify the risk factors of metabolic syndrome and the adjusted relative risk (RR) was calculated. Results: The cohort included 916 women, and 286 (31.2%) of them have metabolic syndrome. MetS was associated with lack of paid work (RR 1.49; 95% CI 1.14-1.95), marital status of without a partner (RR 1.33; 95% CI 1.03-1.72), low educational level (less than 8 years of schooling [RR 1.72; 95% CI 1.23-2.41], 8 to 12 years of schooling [RR 1.37; 95% CI 1.06-1.76], when compared with more than 12 years of schooling), and teenage pregnancy (RR 2.00; 95% CI 1.45-2.77). There was no association between MetS, and the other covariates studied. Conclusion: Metabolic syndrome in a population of women in the fourth decade of life was associated with lack of employment, lack of a partner, low educational level, and teenage pregnancy.